Organisational Predators of Workplace Deviant Behaviour in Hotel Industry - Ojo, Bello Yekinni; Tamunoipiriala, Dan-Jumbo Comfort (Journal of Tourism Management Research, 2019)
Counterproductive behaviour exhibited by hotels workers in Port Harcourt is alarming. Despite the consequences of deviant acts, operators of the hotel industry in Port Harcourt are less minded on the organizational antecedents of workplace deviant behaviour. This study proposed an integrated model that explains the relationship between organizational predators and workplace deviant behaviour (OP-WDB) in the hotel industry in Port Harcourt. The study used a structured questionnaire and sampled 138 hotel staff in Port Harcourt. Pearson Moment Correlation analysis was used. The result shows that four of the six organisational predictors have a positive and significant relationship with deviant behaviour in respect of hotels in Port Harcourt. The F- statistic was statistically significant indicating a valid model. It is recommended that hotel managers should promote the cordial relationship between managers and their subordinates for enhanced employee’s civility behaviour. In addition, hotel owners and managers should formulate policies that can forestall a positive hotel work climate for employees. Once more, hotel managers should ensure that daily employee’s activities are scientifically measured to avert cases of work overload. Finally, hotel managers should lead by example and ensure that employees’ trust in management is total.